2019
DOI: 10.2478/helm-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

Community of Monogenea in populations of Cichla monoculus from two tributaries of the Amazon River in the Northern Brazil

Abstract: SummaryThis study compared the monogeneans community in C. monoculus from the Tapajós River (state of Pará) and Jari River (state of Amapá), northern Brazil. A total of 2188 monogeneans belonging to eight taxa were collected from the gills of fish: Gussevia arilla, Gussevia longihaptor, Gussevia tucunarense, Gussevia undulata, Sciadicleithrum ergensi, Sciadicleithrum umbilicum, Sciadicleithrum uncinatum and Tucunarella cichlae. Gussevia arilla was the dominant species for C. monoculus from the Tapajós River ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(43 reference statements)
0
1
0
1
Order By: Relevance
“…Finally, the positive correlation between populations of monogeneans has been previously reported between Gussevia tucunarense and Gussevia arilla in cichlid fish ( Cichla monoculus ), with a Spearman’s correlation coefficient of up to 0.69. These data suggest that there is no competition between these species [ 40 ]. It has been reported that in the presence of elevated nitrogenous compounds in the water, the cells rich in mitochondria and chlorides increase in count, in addition to the fact that the gills present lamellar fusion; this leads to a decrease in the number of functional Cl − /HCO3 − and to a state of alkalosis in fish, facilitating the colonization and proliferation of parasites such as monogeneans, which usually attack the anatomical branchial region.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the positive correlation between populations of monogeneans has been previously reported between Gussevia tucunarense and Gussevia arilla in cichlid fish ( Cichla monoculus ), with a Spearman’s correlation coefficient of up to 0.69. These data suggest that there is no competition between these species [ 40 ]. It has been reported that in the presence of elevated nitrogenous compounds in the water, the cells rich in mitochondria and chlorides increase in count, in addition to the fact that the gills present lamellar fusion; this leads to a decrease in the number of functional Cl − /HCO3 − and to a state of alkalosis in fish, facilitating the colonization and proliferation of parasites such as monogeneans, which usually attack the anatomical branchial region.…”
Section: Discussionmentioning
confidence: 99%
“…вільно плаваючі личинки вкриті війчастим епітелієм, мають розвинені очі інвертованого типу, на задньому кінці тіла є зачаток апарату кріплення з гачками, який має назву церкомер [27][28][29][30]. У світовій літературі нараховується достатня кількість публікацій, що присвячені проблемам хвороб риби, спричинених одноклітинними організмами, цестодами, трематодами, нематодами, п'явками та крустацеозами [11-23], водночас бракує даних щодо поширення хвороб, викликаних моногенетичними присисними організмами.…”
unclassified